On subordination results for classes of analytic functions with a convolution structure - Prajapat, J. K.; Raina, R. K. (Mathematica Scandinavica, 2010)
By adapting a familiar convolution structure of analytic functions, we define and investigate in this paper certain new classes of analytic functions. Among the various results studied (by using the methods of differential subordinations) are some of the useful properties and characteristics attributed to these function classes. Several consequences of the main results are considered and relevant connections with some known results are also pointed out.